Isothermal Amplification Technology for Disease Diagnosis - Poramin Boonbanjong; Kiatnida Treerattrakoon; Wassa Waiwinya; Piyawat Pitikultham; Deanpen Japrung (Biosensors, 2022)
Isothermal amplification (IA) is a nucleic acid amplification technology (NAAT) that has contributed significantly to the healthcare system. The combination of NAAT with a suitable detection platform resulted in higher sensitivity, specificity, and rapid disease diagnosis. Traditional NAAT, such as polymerase chain reaction (PCR), is widely applied in the general healthcare system but is rarely accessed in resource-limited hospitals. Some IA methods provide a rapid, sensitive, specific, and simple method for disease diagnosis. However, not all IA techniques have been regularly used in clinical applications because different biomarkers and sample types affect either the enzyme in the IA system or sample preparation. This review focuses on the application of some IA techniques that have been applied in the medical field and have the potential for use at points of care.